Formulation and Evaluation of Aromatherapy Roll-On Combining Lemongrass Oil (Cymbopogon winterianus) and Peppermint Oil (Mentha piperita L.) - Nuradnin Hasan; Siti Mutripah; Muhammad Heykal Putra (Jurnal EduHealth, 2026)
Aromatherapy is a method of treatment using scents derived from essential oils. Lemongrass oil can be used in aromatherapy because it has calming properties. Peppermint oil contains the main compound menthol, which is useful as a diuretic, antispasmodic, antiinfective, analgesic, and anxiety reliever. This study aims to formulate and evaluate a roll on aromatherapy combination of lemongrass oil and peppermint oil. The combination of lemongrass oil and peppermint oil was formulated in the form of a roll-on aromatherapy preparation, then evaluated for its physical properties, including organoleptic, homogeneity, pH, and hedonic tests. The results show that the combination of lemongrass oil and peppermint oil can be formulated into an aromatherapy roll on preparation with homogeneous physical properties, a clear yellowish color, a lemongrass aroma, a liquid consistency, and a warm and cool taste or sensation, as well as a pH of 6. In the hedonic test, the preparation received good and acceptable scores from respondents for color, consistency, and taste or sensation. Therefore, it can be concluded that lemongrass oil and peppermint oil can be formulated into an aromatherapy roll on preparation and meet the evaluation standards for aromatherapy roll on preparations.